Ischemic Heart Disease during Acute Exacerbations of COPD - Rosa Malo de Molina; Silvia Aguado; Carlos Arellano; Manuel Valle; Piedad Ussetti (Medical Sciences, 2018)
Patients with chronic obstructive pulmonary disease (COPD) have a higher risk of acute cardiovascular events, and around 30% die from cardiovascular diseases. Recent data suggest an increased risk of myocardial infarction in the following days of a severe exacerbation of COPD. Disruption in the balance during the exacerbation with tachycardia, increased inflammation and systemic oxidative stress as well as some other factors may confer an increased risk of subsequent cardiovascular events. A number of investigations may be useful to an early diagnosis, including electrocardiography, imaging techniques and blood test for biomarkers. Some drugs that have changed prognosis in the cardiovascular setting such as cardioselective beta-blockers may be underused in patients with COPD despite its demonstrated benefits. This review focuses on several aspects of exacerbation of COPD and cardiovascular events including epidemiology, possible mechanism, diagnosis and treatment.